A turn‐on fluorescent probe based on quinoline and coumarin for rapid, selective and sensitive detection of hypochlorite in water samples. (5th June 2020) - Liu, Ruxin; Zhao, Yuqi; Cui, Xiaoqian; Sun, Xiaoxiao; Fei, Qiang; Feng, Guodong; Shan, Hongyan; Huan, Yanfu
Abstract: A fluorescent probe L ‐Cu 2+ based on quinoline, coumarin and Cu 2+ has been synthesized and characterized for hypochlorite determination. After copper ion was added to the solution of ligand L, the fluorescence quenching at 490 nm might result from a ligand–metal charge transfer (LMCT) process and its strong coordination ability for Cu 2+ . In the presence of hypochlorite, the structure of ligand L was destroyed to form 7‐(diethylamino)‐coumarin‐3‐carboxylic acid, and the fluorescence was restored at 460 nm. In this case, L‐ Cu 2+ complex could be used as a fluorescent probe to detect hypochlorite, with the advantages of rapid, selective, wide linear range and low detection limit.